Banachs space: Lviv and the Scottish Cafe - Henderson, D. (Condensed Matter Physics, 2004)
In a sense Stefan Banach is the patron saint of this workshop. He was one
of the most prominent former residents of Lviv. His “hangout”, the Scottish
Cafe, is shown in the street scene that is the cover of the book of abstracts. По суті, Стефан Банах є покровителем цієї робочої наради. Він був одним з найвидатніших мешканців Львова. Шотландське кафе, завсідником якого він був, є показане на панорамі вулиці, що є титульною сторінкою збірки тез робочої наради.